The use of the granite cut residue (GCR) as an admixture in the mechanical properties of concrete - Gonçalves, Jardel Pereira (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The use of waste and industrial by-products in the building sites seems to be an excellent alternative to decrease the environmental impact of the industry as well as to contribute to sustainable development. The granite cut residue (GCR) is a result of the process of sawdusting rock blocks into plates using an equipment called loom. In Brazil, the estimated amount of residue produced annually is 165.000 tons. This article described a study in which GCR physical and chemical characterisation was carried out. Tests to evaluate the potential oxidation of existing Fe in the GCR were also performed. The results of the use of the GCR as an admixture in concrete in fractions of 10% and 20% of the cement mass are presented. The compressive strength, flexural and split tensile strength of concrete were evaluated. The analysis of the results led to the conclusions that the GCR can be classified as class II residue (noninert), that its use as an admixture in concrete production is technically feasible, and also that the best performance is achieved with an admixture ratio of 10%.